Best practice in the assessment of bladder function in infants - Luis Guerra; Michael Leonard; Marco Castagnetti (Therapeutic Advances in Urology, 2014)
The purpose of this article is to review normal developmental bladder physiology in infants and bladder dysfunction in conditions such as neurogenic bladder, posterior urethral valves and high grade vesicoureteric reflux. We contrast the classical concept that bladder function in nontoilet-trained children is thought to be ‘reflexive’ or ‘uninhibited’, with the results of more recent research showing that infants most commonly have a stable detrusor. The infant bladder is physiologically distinct from the state seen in older children or adults. The voiding pattern of the infant is characterized by an interrupted voiding stream due to lack of proper urinary sphincter relaxation during voiding. This is called physiologic detrusor sphincter dyscoordination and is different from the pathologic ‘detrusor sphincter dyssynergy’ seen in patients with neurogenic bladder. Urodynamic abnormalities in neonates born with spina bifida are common and depend on the level and severity of the spinal cord malformation. Upper neuron lesions most commonly lead to an overactive bladder with or without detrusor sphincter dyssynergy while a lower neuron lesion is associated with an acontractile detrusor with possible denervation of the external urinary sphincter. In infants with neurogenic bladder, the role of ‘early prophylactic treatment (clean intermittent catheterization and anticholinergics)’ versus initial ‘watchful waiting and treatment as needed’ is still controversial and needs more research. Many urodynamic-based interventions have been suggested in patients with posterior urethral valves and are currently under scrutiny, but their impact on the long-term outcome of the upper and lower urinary tract is still unknown. Cumulative data suggest that there is no benefit to early intervention regarding bladder function in infants with high-grade vesicoureteric reflux.